Copper and zinc isotope ratios in human bone and enamel. Issue 3 (17th November 2016) - Jaouen, Klervia; Herrscher, Estelle; Balter, Vincent
Abstract: Objectives: Here, we report Cu and Zn isotope ratios of bones and teeth of French people from various historical periods with the aim to understand how Cu and Zn isotope ratios of bone, a tissue that is continuously remodeled throughout life but that is prone to post‐mortem diagenesis, compare with that of tooth enamel, a tissue that forms once during childhood but that is more resistant to diagenesis. Specifically, we examine (1) the potential existence of sex‐related differences in the Cu isotope ratios (represented as δ 65 Cu) in the tooth enamel of identified men and women, and (2) a decrease of Zn isotope delta ratios (represented as δ 66 Zn) related to the increase of meat and fish consumption during the 20 th century. Methods: Four series of material were studied: the archeological population of Saint‐Laurent de Grenoble (17 th –18 th centuries AD), an anatomical collection of skulls (19 th century AD), a contemporary anatomical collection of bones never buried, and contemporary teeth samples. The metals were purified by liquid chromatography and their isotopic ratios measured by means of multicollector inductively coupled plasma mass spectrometry. Results: We describe a clear offset between bone and tooth enamel for Zn isotope ratios, as previously observed in animals. There is a similar offset for Cu isotope ratios. We did not observe any difference between the δ 65 Cu values of men and women when looking at dental enamel. For the contemporary samples, the δ 66 Zn values of bioapatite decreased, which might be explained by the increase of animal product consumption among the French people during this period, notably when the access to seafood became widespread. Conclusions: Our study demonstrates that the Cu and Zn isotope compositions of dental enamel are promising tools for childhood diet reconstruction. Meanwhile, the Cu isotope ratio of tooth enamel is unlikely to be useful for the identification of biological sex, even in the case of populations with early menarche. Further works are needed to understand the relationships between trophic level and Zn isotope ratios of human remains.